(3ehShYI GdSjfeG (B:s (3TjQeQ GdLRA GdKGfj (B/s - (3LQGfJ, HGQD cjKs; (3CMeO jhSas ((3GdbGgQI (B:s (3GdeQcR Gdbhej ddJQLeI ,s, 2015)
(3JgOa ehShYI GdSjfeG (B((3TjQeQ(B) (3Edi Cf Jchf YedG eQLYjG aj eLGd GdOQGSGJ GdSjfeGFjI, hgj eUeeI dcj JdHj EMJjGLGJ GdbGQF GdYGe, hWdHI GdLGeYGJ hGdeYGgO, HCf JbOe fXQI YGeI TGedI heagheI dJGQjN hfXQjI GdSjfeG, eY GdJCcjO Ydi GdLGfH GdCeQjcj(B. (3hSha jLO GdbGQF aj GdehShYI GdMbGFb GdCSGSjI Mhd JQGjN GdSjfeG, hTQMG hGVMG ddeaGgje hGdNWhW GdfXQjI GdCSGSjI, hOdjdG Edi GdeLGOdGJ GdegeI Mhd gPG GdehVhY, hGdehShYI JJfGhd GdSjfeG HhUagG afG, hJQajgG, hUfGYI, hgj dPdc JbOe ehGOG Mhd cd GdCfeGW GdajdejI GdegeI, hTQcGJ GdEfJGL, hUfGYGJ GdSjfeG aj GdHdOGf GdeNJdaI, HGdEVGaI Edi GdehVhYGJ GdJbfjI hGdUfGYjI PGJ GdYdGbI, hGdeSGFd GdKbGajI, hGdeYGdLGJ GdfbOjI ddSjfeG(B.s
Keywords: (3TjeQ s; (3ehShYI GdSjfeG s; (3ehShYI s